Quality assessment of semolina pasta incorporated with Gracilaria sp. - Calimpong, Jewenyl Elaiza Bito-onon
The study aimed to develop a chicken gravy formulation using jackfruit seed flour. Four formulations of chicken gravy (10%, 25%, 50% and 100%) were produced and underwent sensory evaluation tests. Rank tests for preference and general acceptability test were used to determine the Most Preferred Formulation (MPF). Chicken gravy from the MPF was then subjected to physic-chemical tests such as determination of pH, total soluble solids, titrable acidity, viscocity, crude fat, and crude protein, and sensory evaluation. Results of sensory evaluation for the determination of the most preferred formulation (MPF) using Rank for Preference and General Acceptability tests revealed F3 (50% JFSF) as the most preferred formulation. F3 was then subjected to the second phase of sensory evaluation using descriptive analysis (15-cm line scale), paired preference test with the control (0% JFSF) and consumer test involving 50 panelists taken from students of UPV. Descriptive analysis revealed that F3 has an over-all acceptability of like moderately (median score= 3) where it obtained ratings of the following attributes using a 15-cm line scale: color (6.37 cm), mouth feel (5.15 cm), flavor (4.28 cm) and consistency (6.91 cm). Paired preference test revealed that F3 is more acceptable than the control (median ranks of 16: 23). In consumer test, F3 was rated as like very much (46%). Results of the physico-chemical analyses suggest that F3 had a mean pH of 5.56, total soluble solids (TSS) of 10.72, a titrable acidity (TA) of 0.07%, a viscocity of 3.31, a crude fat content of 10.51%, and a crude protein content of 1.36%. The results of the physico-chemical tests on f3 gravy formulation show that jackfruit seed flour can indeed be used in the production of chicken gravy. Further, results suggests that jackfruit seed flour has a potential to be a good emulsifier and thickening agent and further studies can delve on its potential as a versatile food ingredient.